The tiny seed [anglicky] - Carle, Eric, 1929-2021 (Puffin, 1997)
A classic picture book by Eric Carle - The Tiny Seed. When the tiny seed is blown away from its parent plant, it travels a very long way - over seas, deserts and mountains. The tiny seed survives the hazards of the journey and finally falls onto fertile earth. It grows and grows, becoming the tallest, biggest flower for miles around. Then one day the wind blows and thousands of the flower's seeds begin their own journeys. Eric Carle is an internationally bestselling and award-winning author and illustrator of books for very young children. Eric lives in Massachusetts with his wife, Barbara. The Carles opened The Eric Carle Museum of Picture Book Art in Massachusetts in 2002.